Business Strategy Formulation By Shareholders and Company Management using The Analytical Network Process (ANP) - Faizal Faizal; Achsanul Qosasi; Antonius W. Sumarlin; Erwin Permana; Gatot Hendro Prakosa; Indriana Indriana; Glory Aguzman (Bina Nusantara University, 2016)
This research aimed to identify the business strategy formulation by the shareholders and the management of the company. Ten companies were selected to be the objects of this research. Those companies were the information technology, telecommunication, printing, mining, construction and chemical companies in Indonesia. The research was conducted by using the Analytical Network Process (ANP) and considering the chosen respondents as the decision makers (experts) of those companies. The respondents were chosen by using the non-probabilitty sampling method. The result shows that the roles of the company managements are considered m ore influental (0,57143) than the roles of the shareholders (0,28571). From the output of stakeholder’s condition, the best-stratified priority strategies are differentiation (0,600515), cost of leadership (0,230754) and focus (0,168731).